Oxford handbook of cardiac nursing - Olsen, Kate, 1967- ([Oxford] : Oxford University Press, 2014)
This handbook provides a systematic account of the main areas of cardiac nursing including assessment, investigation, treatment, rehabilitation, and pharmacological interventions. Cardiac nurses in all settings will find this a practical and evidence-based summary of the relevant issues.
Description based on online resource; title from home page (viewed on January 30, 2014).
Keywords: Heart -- Diseases -- Nursing; Cardiovascular system -- Diseases -- Nursing